EFEKTIVITAS KAMPANYE #BUDAYABEBERES OLEH KENTUCKY FRIED CHICKEN (KFC) INDONESIA TERHADAP SIKAP KONSUMEN REMAJA DENPASAR - Ramindra, Lintang Pratama Lian; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
KFC is the most mainstream drive-thru eatery in Indonesia where i 24 million individuals are keen i on i KFC.2019, KFC appealed to the public to dispose of their leftovers independently by using the #budayabeberes campaign which they spread through social media as well as at employee outlets. The theory utilized in this research is Dennis Mcquail's Stimulus Organism Response theory. This examination is a quantitative research. The discoveries in this investigation the viability of the #budayaberes crusade did by KFC has an impact of i 65.9% i on the attitudes of KFC customers in Denpasar, while i 24.1% is affected by different factors. The adequacy of the #budayabeberes crusade by Kentucky Fried Chicken (KFC) Indonesia in Denpasar, Bali gives a compelling impact on the perspectives of Denpasar youth buyers. Which expresses that the test worth of the coefficient of assurance is i 65.9%, where the worth is remembered for the solid or successful classification. Keywords : Campaign, KFC, #budayabeberes